Körperkonzepte (Böhlau, 2025)
Concepts of the Body - Transformations in Slavic Literatures and Cultures refers to the corporeal turn and examines the representation of bodies and related cultural discourses from an interdisciplinary perspective. The volume focusses on transformations, i.e. conceptual changes in the artistic view of the body that were effected by historical events such as wars and migrations movements, scientific discoveries or social changes. The contributions highlight the interplay between artistic innovation and the political positioning of writers, artists and activists on relevant contemporary issues.